Effect of Rhesus Negative in Pregnancy - Khatun, Jamila; Begum, Ruly (Medicine Today, 2018)
Hemolytic disease of the newborn due to Rhisoimmunisation is a major cause to perinatal morbidity & mortality. Erythroblastosis fetalis is a disease of fetus and newborn due to incompatibility between fetal and maternal blood group. Diagnosis and therapy for Rh immunization improved considerably. Its prevention by immunoprophylaxis has been responsible for the reduction in the incidence of perinatal mobility. Still Rh immunization and erythroolastosis fetalis is responsible for many obstetric mishaps in our country. To see the pregnancy outcome of Rhesus negative women. This prospective study was carried out from October 2013 to March 2014 in Obstetrics & Gynecology department of Sylhet MAG Osmani Medical College & Hospital, Sylhet. 50 Rh-negative pregnancies were selected those who got admitted in department of Obstetrics & Gynecology, SOMCH. 30.62% of the fetuses had blood group B+ve, 24.40% 0+ve and 20.40% A+ve. Regarding the perinatal outcome 76% were healthy, 4% still birth, 4% neonatal death, 14% with erythroblastosis foetalis and 4% developed hydrops. Mild anaemia and oedema was common in primi and multigravida patients. PET was found 6.2% in multigravida patients. APH and Hydramnios with congenital anomalies were 3.1% and 3.1% respectively. This study was undertaken to evaluate the outcome of pregnancy in Rh -ve women. It is preventable. Primary prevention of isoimmunization by giving combined antenatal and postnatal prophylaxis. Medicine Today 2018 Vol.30(1): 23-25